Effect of Fe2+/3+ and Cu2+ Ions on Spectral Properties of Type I Collagen - Zhang1, Ju-Cheng; Yan1, He-Ping; Zhang1, Guo-Wei; Chen1, Xianlan; Zhang2, Li; Liu1, Wei (Asian Journal of Chemistry, 2013)
The effects of Fe3+, Fe2+ and Cu2+ ions on type I collagen were investigated by UV-visible and fluorescence spectra. The UV-visible spectra revealed that the Fe3+ ion can cause the 270 nm absorbance peak of type I collagen decreased, but Fe2+ and Cu2+ enhanced this peak. The fluorescence emission spectrum of the type I collagen show two emission band centered at 307/278 nm and 380/295 nm, adding Fe3+ will enhanced the intensity of emission band both 307 and 380 nm. However, adding Fe2+ and Cu2+ ions can not cause the two fluorescence peak enhanced evidently. The 380 nm fluorescence peak increased in presence of Fe3+ suggested the Fe3+ could induce pyridinoline crosslink formed in collagen solution.